A resistive heating system for homeothermic maintenance in small animals - Kersemans, V; Gilchrist, S; Allen, P; Beech, J; Kinchesh, P; Vojnovic, B; Smart, S (Elsevier, 2015)
Purpose To develop an MR-compatible resistive heater for temperature maintenance of anaesthetized animals. Materials and Methods An MR-compatible resistive electrical heater was formed from a tightly-wound twisted pair wire, interfaced to a homeothermic maintenance controller. Fat-suppressed images and localized spectra were acquired with the twisted pair heater and a near-identical single strand heater during operation at maximum power. Data were also acquired in the absence of heating to demonstrate the insensitivity of MR to distortions arising from the passage of current through the heater elements. The efficacy of temperature maintenance was examined by measuring rectal temperature immediately following induction of general anesthesia and throughout and after the acquisition of a heater artifact-prone image series. Results Images and spectra acquired in the presence and absence of DC current through the twisted pair heater were identical whereas the passage of current through the single strand wire created field shifts and lineshape distortions. Temperature that is lost during anesthesia induction was recovered within approximately 10–20 minutes of induction, and a stable temperature is reached as the animal's temperature approaches the set target. Conclusion The twisted pair wire heater does not interfere with MR image quality and maintains adequate thermal input to the animal to maintain body temperature.